Evaluasi Efektivitas Penggunaan Aplikasi Accurate Online dalam Penyusunan Laporan Keuangan (Studi Kasus Pada PT Kiat Rancang Bangun Properti di Balikpapan) - Andira Nazwa; Yanzil Azizil Yudaruddin; Dika Karlinda Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Evaluation of the Effectiveness of Using Accurate Online Application in the Preparation of Financial Statements (A Case Study at PT Kiat Rancang Bangun Properti in Balikpappan City). Supervisors: Yanzil Azizil Yudaruddin and Dika Karlinda Sari. This study aims to evaluate the effectiveness of using the Accurate Online application in the preparation of financial statements at PT Kiat Rancang Bangun Properti in Balikpapan City. This research employs a descriptive method with a qualitative approach in the form of a case study. Data were collected through observation, questionnaire distribution, and interviews with participants directly involved in the recording and preparation of the company’s financial statements. The results of the study indicate that the use of the Accurate Online application at PT Kiat Rancang Bangun Properti has generally been effective in improving efficiency and facilitating financial recordkeeping. In terms of user experience and the quality of financial statements, the Accurate Online application falls into the effective category, although it has not yet been fully optimal. Meanwhile, in terms of efficiency, Accurate Online is categorized as very effective because it is able to accelerate the process of preparing financial statements through an automated system, even though the company still implements double recording as a form of internal control.